2020
DOI: 10.1016/j.jocn.2020.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage caused by COVID-19: Change in volume and spectrum of neurosurgery patients

Abstract: Background: There has been a dramatic change in the pattern of patients being seen in hospitals and surgeries performed during the ongoing COVID-19 pandemic. The objective of this study is to study the change in the volume and spectrum of surgeries performed during the ongoing COVID-19 pandemic compared to pre-COVID-19 era. Methods: Details of all patients who were operated under department of neurosurgery at our institute since the onset of COVID-19 pandemic in India were collected and compared to the same ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(101 citation statements)
references
References 22 publications
6
94
0
1
Order By: Relevance
“…On analyzing our operative workload by specialty, a decrease in the number of cases was noted across all specialties compared with before the COVID-19 pandemic 4 in concordance with the findings reported by Jayakumar et al. 1 The number of neuro-trauma cases had decreased owing to the decreased number of road traffic accidents, which had resulted from the reduced vehicle movement during the lockdown.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…On analyzing our operative workload by specialty, a decrease in the number of cases was noted across all specialties compared with before the COVID-19 pandemic 4 in concordance with the findings reported by Jayakumar et al. 1 The number of neuro-trauma cases had decreased owing to the decreased number of road traffic accidents, which had resulted from the reduced vehicle movement during the lockdown.…”
supporting
confidence: 87%
“…Our operative workload reflected this change in nonemergent OPD volumes. 4 5 During the lockdown period in 2020 (March 25 to May 31, 2020), 53 surgeries (47 emergency and 6 routine) had been performed compared with 111 (47 emergency, 64 routine) during the same period in 2019. Furthermore, the number of surgeries performed per week had declined steadily as the number of COVID-19 cases increased in the state [rs(8) = −0.914; P = 0.000].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors analyzed our department data between March 25 and May 31, 2020 and compared with the same time period last year. 10 , 14 We observed that during these 10 weeks of pandemic in 2020, only 53 surgeries were performed compared with 111 during the same period last year, representing a decrease of 52.2%. The majority of cancelled/postponed cases were “routine/nonemergent.” In total, 11.3% patients operated during COVID-19 pandemic were nonemergent surgeries compared with 57.5% in the pre–COVID-19 era ( P = 0.000).…”
Section: Resultsmentioning
confidence: 83%
“…As a response to COVID-19 pandemic, hospitals and medical institutions have had to adapt to the “new normal” by doing widespread COVID-19 testing, 9 switching from a physical outpatient department to telemedicine, and rescheduling of “non-emergent” surgeries. 10 Hospitals have been forced to ration materials and human resources. Hospital beds, ventilators, and monitors are being reserved for patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%